TIPE PARTISIPASI POLITIK PEREMPUAN PADA PEMILIHAN LEGISLATIF TAHUN 2019 DI KABUPATEN BOMBANA - Rahmat Hidayat; Irawati; Hasnidar (Halu Oleo University, 2023)
The role of women in politics in almost all countries experiences obstacles, especially in developing countries, with both structural and cultural constraints. The structural constraints referred to are the level of education, economy, work of housewives, child care, and kitchen work. This work is identified as a second-class job that is difficult to balance with men when it comes to involvement in the public sector. While cultural constraints are cultural factors that place women in a private space where they have to live at home, women are always perceived as serving the family. Bombana District is one of the areas with a high level of female voter turnout and abstention for female voters. This study aims to determine the type of female voter participation in the 2019 legislative elections in Bombana District. The method used in this research is descriptive qualitative. The types and sources of data in this study are using primary data and secondary data with observation data collection techniques, interviews, and documentation. The results of this study indicate that the type of participation of female voters in the 2019 legislative elections in Bombana uses two types of participation, namely the type of passive participation and the type of golput participation.